Strategy for Strengthening Restorative Justice Policy in Resolution of Land Disputes in Indonesia: Strategy for Strengthening The BPN Institution - Agung Iriantoro; Agus Surono; Zaitun Abdullah; Rahmat Rahmat (Universitas Islam Sultan Agung, 2026)
Land dispute resolution in Indonesia faces multi-dimensional complexity stemming from unclear land boundaries, overlapping ownership rights, and conflicts between indigenous communities and the state. Regulation of the Minister of Agrarian Affairs and Spatial Planning/National Land Agency (Permen ATR/BPN) No. 21 of 2020 introduces a mediation mechanism based on restorative justice principles as an alternative non-litigation dispute resolution that focuses on restoring social relations and reaching consensus in accordance with local wisdom. This study uses a qualitative approach with data were collected through in-depth interviews with BPN officials, mediators, and related parties; direct observation of the mediation process; and a study of regulatory documents and implementation reports. Key findings reveal that while mediation success rates can reach 28.5% to 55-65% in areas with integrated customary deliberations, optimal implementation is still hampered by institutional structural gaps, heterogeneity in mediator capacity with only 45% certified, weak legal force of mediation outcomes that allows for the cancellation of 25% of agreements, informal cross-institutional coordination, and limited technology utilization. Policy strengthening requires a holistic approach that integrates institutional restructuring with the establishment of dedicated mediation units, the development of multi-layered competency standards, strengthened regulations with executive powers, formalization of cross-institutional coordination including legal recognition of customary deliberations, and optimization of JUSTISIA technology. Socio-legal implications indicate that restorative justice contributes significantly to reducing social tensions and increasing institutional trust, particularly by integrating local wisdom.